The Influence of E-Service Quality, Interactive Features and E-Satisfaction on Shopee E-Commerce Customer Loyalty among Students of Sumbawa University of Technology - Debora Astin Masangin; Wilia Ismiyarti (Escalate : Economics and Business Journal, 2026)
The increasing competition in the e-commerce industry requires platforms to strengthen customer loyalty. This study examines the effect of e-service quality, interactive features, and e-satisfaction on customer loyalty toward Shopee e-commerce among students of Sumbawa University of Technology. This research uses a quantitative approach with a survey method. Data were collected from 170 Shopee users selected through purposive sampling and analyzed using multiple linear regression analysis. The results show that e-service quality, interactive features, and e-satisfaction have a positive and significant effect on customer loyalty, both partially and simultaneously. These findings indicate that improvements in electronic service performance, engaging interactive features, and higher customer satisfaction significantly increase customer loyalty toward Shopee. This study provides empirical evidence for e-commerce platforms in designing strategies to enhance customer loyalty, particularly among university students.